2001
DOI: 10.1111/j.1365-2621.2001.tb16116.x
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying and Surface Properties of Wheat Gluten under Acidic Conditions

Abstract: The solubility of wheat gluten was greatly improved at pH 4 or lower where it showed good emulsifying activity. This might be due to its high surface activity in the acidic pH range and the formation of a stable protein film surrounding the oil droplets. Among the major gluten proteins, gliadins showed higher surface activity than glutenins. The content of glutenins in the adsorbed protein film was higher than that of gliadins, and glutenins are likely to have been adsorbed more tightly than gliadins. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 22 publications
3
46
0
Order By: Relevance
“…Fat (Euston 1997;Innocente et al 1999), whey protein (Zayas 1997;Takeda et al, 2001;Aryana et al 2002), soy proteins (Aoki et al 1980;Yao et al 1990;Rir et al 1994) and carbohydrates (Garti et al 1997;Chouard 2004). Many ingredient manufacturers have challenged themselves to develop low-cost egg alternatives to be used in dairy-based desserts, i.e., ice cream.…”
Section: Introductionmentioning
confidence: 99%
“…Fat (Euston 1997;Innocente et al 1999), whey protein (Zayas 1997;Takeda et al, 2001;Aryana et al 2002), soy proteins (Aoki et al 1980;Yao et al 1990;Rir et al 1994) and carbohydrates (Garti et al 1997;Chouard 2004). Many ingredient manufacturers have challenged themselves to develop low-cost egg alternatives to be used in dairy-based desserts, i.e., ice cream.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmedna et al 14 have shown that the solubility of some non‐gluten proteins did not change drastically on changing the pH from 4.5 to 8.5. In our case the control was least soluble from pH 6 to 8, similar to previously reported results 13. At pH 3 and 4, jet‐cooked samples showed a significant increase in solubility as compared with the control.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymatic hydrolysis8–11 and chemical phosphorylation using POCl 3 12 are some other reported ways to modify the functionality of wheat gluten. Takeda et al 13 evaluated the emulsifying and surface properties of wheat gluten under acidic conditions. Solubilised wheat protein isolate (SWPI) was evaluated and compared with other proteins for functional properties by Ahmedna et al 14 Normally, the functional properties of proteins are optimum near the isoelectric point (IP).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented (Tsen, 1966;Wehrle et. al.,1997;Takeda et. al., 2001; and supported by the findings of the many rheological studies which indicated differences between the nonacidified and chemically or biologically acidified doughs (Clarke et.…”
Section: Effects Of Lab To Dough Structurementioning
confidence: 99%